Late erosion of an Adjustable Transobturator Male System (ATOMS®) device - Jessica A Paynter; Kirby R Qin; Justin Chee; Todd Manning; Janelle Brennan (IJU Case Reports)
Introduction This report describes late erosion of an Adjustable Transobturator Male System device which was inserted for post‐prostatectomy incontinence. The Adjustable Transobturator Male System device eroded the bulbar urethra 5 years post insertion, despite initial improvement of symptoms. Case presentation Following an open radical retropubic prostatectomy, a 64 year‐old male patient developed post‐prostatectomy incontinence. He had a known urethral stricture and had also undergone salvage radiotherapy for biochemical recurrence of prostate cancer. His incontinence was initially successfully treated with an Adjustable Transobturator Male System device, yet this eroded his bulbar urethra 5 years post insertion, which was deemed to be a late erosion. Conclusion Urologists should be aware that late erosion of the Adjustable Transobturator Male System device can occur, and risk stratification of patients undergoing Adjustable Transobturator Male System device insertion may help to minimize erosion rates.